1990
DOI: 10.1007/bf02156267
|View full text |Cite
|
Sign up to set email alerts
|

Abdominoperineal resection for severe perianal Crohn's disease

Abstract: Despite the high incidence of involvement of the perianal region in Crohn's disease, excisional surgery seldom is required for perianal disease alone. Nine patients are presented who had severe perianal Crohn's disease, which eventually required abdominoperineal excision of the anorectum. In all nine patients, it was secondary manifestations of anal Crohn's disease that precipitated proctectomy, such as high fistulas, strictures, and rectovaginal fistulas. These secondary phenomena, especially fistulas caused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Proctectomy was necessary in two of our patientsone with severe anal stenosis and the other with intractable high grade proctitis. However, this low number may not reflect the overall proctectomy rate in patients with distal Crohn's colitis or perianal disease, which is probably higher.2 [15][16][17] The indications for a more aggressive surgical approach to treat perianal fistulas is a major point of discussion. With various surgical procedures (fistulotomy, partial fistulotomy, drainage), high healing rates were achieved (up to 85%) in selected groups of patients.10 13 16 18-24 Some of these papers reported only operations on active fistulas,22 others only in patients where an aggressive surgical approach seemed advisable (low lying fistulas and absence of rectal disease as evidenced by rates of rectal involvement in the studied patients as low as 30%,23 as opposed to 61% rectal involvement in our patients).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proctectomy was necessary in two of our patientsone with severe anal stenosis and the other with intractable high grade proctitis. However, this low number may not reflect the overall proctectomy rate in patients with distal Crohn's colitis or perianal disease, which is probably higher.2 [15][16][17] The indications for a more aggressive surgical approach to treat perianal fistulas is a major point of discussion. With various surgical procedures (fistulotomy, partial fistulotomy, drainage), high healing rates were achieved (up to 85%) in selected groups of patients.10 13 16 18-24 Some of these papers reported only operations on active fistulas,22 others only in patients where an aggressive surgical approach seemed advisable (low lying fistulas and absence of rectal disease as evidenced by rates of rectal involvement in the studied patients as low as 30%,23 as opposed to 61% rectal involvement in our patients).…”
Section: Discussionmentioning
confidence: 99%
“…Proctectomy was necessary in two of our patients -one with severe anal stenosis and the other with intractable high grade proctitis. However, this low number may not reflect the overall proctectomy rate in patients with distal Crohn's colitis or perianal disease, which is probably higher.2 [15][16][17] The indications for a more aggressive surgical approach to treat perianal fistulas is a major point of discussion. With various surgical procedures ( The results of our prospective follow up indicate that the prognosis of perianal fistulas in Crohn's disease with regard to healing and recurrence may be worse than reported in previous studies.…”
Section: Therapy Of Active Intestinal Diseasementioning
confidence: 99%
“…[2][3][4] The wound remains unhealed in up to 33% of patients at 12 months. 5,6 PPS is reported more frequently after surgery for Crohn's disease than after surgery for ulcerative colitis or anorectal cancer. 5,7,8 The incidence of PPS after abdominoperineal resection for low rectal cancer may be as high as 29%, especially in patients who have received preoperative radiotherapy.…”
mentioning
confidence: 99%
“…Several investigators have suggested that some perineal lesions are associated with delayed perineal healing, including fistulous tracts exiting beyond 5 cm from the anal verge, 10 complex abscesses, and pelvic sepsis. 11 Consideration of the factors identified above that increase the risk of PPS is helpful because they provide additional predictors for determining intraoperative surgical technique and wound management.…”
Section: Discussionmentioning
confidence: 99%